Advanced tubal pregnancy at 34 weeks with eclampsia and HELLP syndrome: a case report and literature re - Yang Liu; Xiaoping Xu; Qian Liu; Xiaolan Luo; Bin Cai; Jingyuan He; Ruiqian Liu (BMC, 2023)
Abstract Background Tubal ectopic pregnancies in the late stages of pregnancy are uncommon, and reports on their complications are scarce. We present the case of a woman who had a tubal ectopic pregnancy at around 34 weeks and developed severe pre-eclampsia complications. Case A 27-year-old woman presented to our hospital several times with vomiting and convulsions. A physical exam revealed hypertension, scattered ecchymosis, and a large abdominal mass. A computed tomography (CT) scan performed in an emergency revealed an empty uterus, a stillbirth baby in the abdominal cavity, and a crescent-shaped placenta. Blood tests revealed that the patient had a low platelet count and clotting dysfunction. Laparotomy confirmed advanced right fallopian tube pregnancy without rupture, and salpingectomy was performed. Pathological examination revealed a significantly thickened tubal wall, adhesion of the placenta, and poor placental perfusion. Conclusion The unusually thickened muscular layer of the tube may be one of the reasons for tubal pregnancy progressing to an advanced stage. Placenta adhesion and the special site to which it is attached reduce the risk of rupture. The detection of a crescent-shaped placenta on imaging may aid in the accurate diagnosis, distinguishing between abdominal and tubal pregnancy. Women with advanced ectopic pregnancy are more likely to develop pre-eclampsia and have poorer maternal-fetal outcomes. These negative outcomes may be influenced by abnormal artery remodeling, villous dysplasia, and placental infarction.